Il paesaggio agrario come componente del giardino storico e il giardino storico come parte del paesaggio agrario: aspetti produttivi e caratteri costruttivi e percettivi da analizzare e valorizzare - Alberta Cazzani (Ri-vista: Ricerche per la Progettazione del Paesaggio, 2015)
In historic gardens the aesthetic/ornamental function was always connected to the productive one, with vegetable gardens, orchards, woods and agricultural areas inserted in the site composition. As Emilio Sereni observed, agricultural landscape was in the garden and at the same time the garden was part of the well designed Italian agricultural landscape. The loss of productive functions in the garden, now considered more for its decorative and recreative role and the transformation of the agricultural landscape, often abandoned or altered by modernization and building development, have significantly changed constructive and perceptive features of historic gardens. This paper considers these landscape transformations and the possible preservation and management strategies to valorize and rehabilitate the productive components of the gardens and the functional and visual relationship between gardens and landscape.